2021
DOI: 10.5603/imh.2021.0046
|View full text |Cite
|
Sign up to set email alerts
|

Physical training and ocular yogic exercise in home: good alternative options to control the high-tension form of primary open angle glaucoma during the repeated COVID-19 waves

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Through the global topology optimization, the smoothing factor in the neural network in the deep learning model is the optimization goal, and the optimal model of index evaluation is constructed [ 24 ]. Set and initialize the evaluation index data of public sports training quality as follows: …”
Section: Implementation Of Public Sports Training Quality Evaluation ...mentioning
confidence: 99%
“…Through the global topology optimization, the smoothing factor in the neural network in the deep learning model is the optimization goal, and the optimal model of index evaluation is constructed [ 24 ]. Set and initialize the evaluation index data of public sports training quality as follows: …”
Section: Implementation Of Public Sports Training Quality Evaluation ...mentioning
confidence: 99%
“…The used Yogic Tratak (continuous gaze to any small point or object following the flame of a candle) can contract and relax the ocular ciliary muscles producing an increase in the aqueous humor outflow; thus, IOP can be reduced in glaucomatous patients [10]. However, the improved IOP in response to Acu-TENS has not been justified in the literature, but the selected BL 61 and BL 62 acupoints for Acu-TENS in this study were based on the study by Yeh et al [21] who reported non-significant changes to IOP in the sham Acu-TENS group while the study group who received the active Acu-TENS showed a significant decline in IOP in both eyes at all different time intervals (immediately, 30 min, and 60 min after a min session of Acu-TENS).…”
Section: Discussionmentioning
confidence: 99%
“…The mainline treatment focuses on the application of IOP-descending eye drops which, despite several drug combinations, do not lower the IOP to the recommended normal range of 10-21 mmHg [7]. To support the usual use of prescribed agents, many patients prefer the complementary therapies [8] for POAG, such as meditation [9], yoga [10], and acupuncture [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation requires long term perseverance, but the positive aspect is that it is flexible and in many cases, e.g. the COVID-19 epidemic where everyone cannot go out [ 17 ], and in the final phase of rehabilitation, etc., remotely supervised online exercise rehabilitation by a physiotherapist is one of the available and recommended home options to continue with the required exercise rehabilitation [ 18 , 19 ]. Balance training is a relatively mature form of rehabilitation training.…”
Section: Introductionmentioning
confidence: 99%